Governance, firm size and innovative capacity: Regional empirical evidence for Germany - Michael Berlemann; Vera Jahn (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
Successful innovation is a precondition for economic prosperity. While various potential determinants of innovative activity have been considered, little empirical evidence is yet available for the influence of firm governance issues. This paper aims at filling this gap in the literature by studying whether the relative importance of owner-managed small and medium sized enterprises has an effect on regional innovative capacity. We therefore combine patent data with data from the firm database of Creditreform, containing information on the governance structure of regional operating enterprises. Using a cross section of German NUTS-3-regions, we identify a significantly positive relation between the relative importance of owner-managed SMEs and innovative capacity. This finding is highly robust when controlling for spatial correlations.
Keywords: O31; C21; D23; 330; innovation; owner-managed firms; SMEs; Germany